A survey of Aedes albopictus (Diptera: Culicidae) distribution in Slovenia in 2007 and 2010 - Katja Kalan; Rok Kostanjšek; Enrih Merdić; Tomi Trilar (Natura Sloveniae)
Spreading of the invasive mosquito species Aedes albopictus in the southwestern part of Slovenia was studied in 2007 and 2010. The study was based on larval and adults search. Mosquito larvae were sampled with a dipper or a net from various artificial containers and the adults caught by human bait catches for 15 minutes. In 2007, the research was carried out in 64 municipalities, where 327 larval habitats were examined. Ae. albopictus was observed in 52 municipalities. Mosquito larvae were most often collected in small containers placed in shady areas. All the adults were caught near breeding sites. The species was found in most of the studied areas in south-western Slovenia, especially in its coastal part and near Nova Gorica. In 2010, a research was implemented in 12 municipalities that had proved negative for Ae. albopictus in 2007. The incidence of Ae. albopictus was surveyed in 100 larval habitats. The presence of Ae. albopictus was confirmed in almost all of the municipalities, which is an indicator of its firm establishment in the studied area.